Pembelajaran Bahasa Arab melalui Pendekatan Komunikatif; Studi Kasus di Pondok Pesantren al-Munawaroh Ngemplak Ngudirejo Diwek Jombang - Baiq Tuhfatul Unsi (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2016)
Arabic capability is an ability which should be mastered by students who follow learning Arabic. Because in learning Arabic, there are four skills that must be mastered by students, among others listening skills, speaking skills, reading skills and writing skills. This four skills is a series of language skills are inseparable from one with another. Of the four skills are an indicator of the success of learning Arabic must not be separated from the appropriate learning methods. Because with the right approach four mahÃ¢rah above can be mastered by students. From this statement, the author conducted research in Islamic boarding school Al-Munawaroh Ngemplak Ngudirejo Diwek Jombang with a focus on Implementation and factor. With descriptive qualitative method is concluded; this Islamic boarding school is successfully practiced in Arabic as the language of daily communication, one of the many Islamic boarding school in Jombang to realize learning Arabic completely through the communicative approach, these are points that must be considered for can be used as a model by institutions other in enhancing learning potential, especially in learning Arabic.